2021
DOI: 10.22460/project.v4i4.p588-594
|View full text |Cite
|
Sign up to set email alerts
|

An Analysis of Figurative Language Found in Song of Bruno Mars Entitled “Grenade”

Abstract: Individuals use language as a means of communication everywhere and at all times. In today's world, figurative language is often encountered in everyday life, such as in song lyrics. Figurative language is a way of describing something without saying it directly. This research aims to investigate the figurative languages found in the lyrics of the song "Grenade" by analyzing their context and attempting to decipher their meaning. The data tool is song lyrics found on the internet, and the research approach is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 7 publications
1
8
0
Order By: Relevance
“…Further, the result of this study is in alignment with the previous studies, particularly those by Lusiana & Qomariana (2017), Dewi, Hidayat & Alek (2020, Yastanti, Suhendar, & Pratama (2018) and Fajrin (2021), who investigated the figurative language from song lyrics, and resulted the research findings that the most dominant figurative languages are hyperbole because the song messages about negative things such as pain heart, and treachery are very deep.…”
Section: Synecdochesupporting
confidence: 89%
See 1 more Smart Citation
“…Further, the result of this study is in alignment with the previous studies, particularly those by Lusiana & Qomariana (2017), Dewi, Hidayat & Alek (2020, Yastanti, Suhendar, & Pratama (2018) and Fajrin (2021), who investigated the figurative language from song lyrics, and resulted the research findings that the most dominant figurative languages are hyperbole because the song messages about negative things such as pain heart, and treachery are very deep.…”
Section: Synecdochesupporting
confidence: 89%
“…Besides, Daniswara, & Winaya (2016) examined the meaning of figurative language with reference to four Iron Maiden's songs. Fajrin & Parmawati (2021) also conducted research analyzing figurative language found in the song of Bruno Mars entitled "Grenade", while Permana & Rajeg (2018) also conducted research entitled figurative language in the song lyrics of Passenger's album "All the Little Lights". Further, other research was also conducted by Yastanti, Suhendar, & Pratama (2018) who investigated figurative language in song lyrics of "Linkin Park".…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, the study draws on the systematic narrative review by Davis et al (2021) to understand the impact of agent persona in learning outcomes, thereby contextualizing the role of figurative language in educational settings. Deameysa et al (2023) and Fajrin & Parmawati's (2021) analyses of figurative language in modern song lyrics offer contemporary examples that parallel the literary depth found in Sherlock Holmes' stories, providing a modern lens through which to view classical literature's enduring relevance. Through a descriptive qualitative methodology, this research aligns with the ethnographic and narrative inquiry approaches exemplified in studies by Hanisfi et al (2022), Hulu et al (2021), and Indarti et al (2023), Figurative language and speech acts in "The Adventures of Sherlock Holmes": A study on descriptive texts offering a comprehensive examination of figurative language's pedagogical implications.…”
Section: Introductionmentioning
confidence: 99%
“…Language, emerging as a system of sound symbols, functions as a fundamental tool for communication, facilitating the exchange of ideas and emotions among individuals (Rohmiyati et al, 2023). It serves not only as a medium for conveying information but also for expressing a wide array of feelings and beliefs, thus enabling a deeper understanding and connection between people (Fajrin, 2021;Mamonto et al, 2023). Language possesses distinct features such as words, sentences, and structures, which are used to articulate thoughts in both written and spoken forms.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation